Reduce the following function using k-map F = wxy + yz + xy’z + x’y

This answer is restricted. Please login to view the answer of this question.

Login Now

Solution:

F = wxyz + wxyz’ + wyz + w’xyz + wx’yz + w’x’yz + wxy’z + wx’yz + w’x’yz + wx’yz’ + w’x’yz’

= wxyz + wxyz’ + w’xyz + wx’yz + w’x’yz + wxy’z + w’xy’z + wx’yz’ + wx’yz’

Now, K-map

User Loaded Image | CSIT Guide

F = x’y + wy  + xz

= y(x + w) + xz

i.e. F = (not x and y) or (w and ) or (w and z)

 

If you found any type of error on the answer then please mention on the comment or report an answer or submit your new answer.
Leave your Answer:

Click here to submit your answer.

Discussion
0 Comments
  Loading . . .